INSTITUTE OF DISSENTING OPINION IN CIVIL AND ADMINISTRATIVE JUSTICE - Gharslyan, Ashkhen (State and Law, 2022)
In the article, the author analyzed the institute of dissenting opinion in civil and administrative justice. The author, in particular, studied the significance and consequences of a dissenting opinion in the process of justice, made the subject of discussion the scope of judicial acts in connection with which a dissenting opinion can be submitted, and also touched upon such theoretical and practical issues as the nature of a dissenting opinion as a procedural document, the need and time of its publication, requirements for the content of a dissenting opinion.